2012
DOI: 10.1177/1721727x1201000113
|View full text |Cite
|
Sign up to set email alerts
|

Oral Focal Mucinosis of the Tongue: A Rare Clinical Case

Abstract: Oral focal mucinosis (OFM) is a rare mucosal lesion of unknown etiopathogenesis. It is considered the oral counterpart of cutaneous focal mucinosis. From the anatomo-pathological point of view it is characterised by a focal degeneration of myxoid type of connective tissue. A literature survey revealed 50 reports of OFM cases worldwide. Here, we present an even more rare case with tongue involvement. Particular emphasis is placed on diagnostic-differential aspects of this kind of lesion, both from the clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It has been reported that, in cancer patients, IL-l~and IL-6 are associated with clinical features of the cachectic condition, such as weakness, loss of appetite, weight loss and sarcopenia (82)(83)(84)(85)(86)(87). Several studies have shown an association between dietary factors and the incidence of cancer.…”
mentioning
confidence: 99%
“…It has been reported that, in cancer patients, IL-l~and IL-6 are associated with clinical features of the cachectic condition, such as weakness, loss of appetite, weight loss and sarcopenia (82)(83)(84)(85)(86)(87). Several studies have shown an association between dietary factors and the incidence of cancer.…”
mentioning
confidence: 99%
“…OFM develops following an excessive secretion of hyaluronic acid and mucoid accumulation between collagen fibers. Ultimately, hyaluronic acid replaces collagen fibers [28][29][30][31]. OFM occurs predominantly in adults during the fourth and fifth decades of life [8].…”
Section: Discussionmentioning
confidence: 99%
“…Nerve sheath myxoma or neurothekeoma has abundant alcianophilic content, numerous mast cells, cells positive for S-100 protein and lobular aspect, differing from the lesion in question. In the same way, it is possible to distinguish OFM from neurofibroma with myxomatous areas [1,12]. Therefore, a routine histological analysis may not always establish the diagnosis of these lesions, due to the similarities among them [10], and complementary histochemical or immunohistochemical analysis is necessary in some cases.…”
Section: Discussionmentioning
confidence: 99%